JUMLAH LEUKOSIT DAN DIFFERENSIASI LEUKOSIT AYAM BROILER YANG DIBERI MINUM AIR REBUSAN KUNYIT - Prastiwanti Nur Jannah; Sugiharto Sugiharto; Isroli Isroli (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
This study aimed to assess the effect of boiled turmeric water on the number of leukocyte and differentiation leukocyte of broilers. The study was conducted in Oktober - November 2016. The material used was 200Day Old Chick  (DOC)  of broiler with initial weight 41.48 ± 0.99 g. Feed used was a commercial feed with code B-11S to phase stater and BR-1AJ for the finisher phase and turmeric. The design used in this study was completely randomized design (CRD) with 5 treatments and 5 replicates containing 8 DOC in each. The treatment consisted of T0 (100% water), T1 (75% water + 25% boiled turmeric water), T2 (50% water + 50% boiled turmeric water), T3 (25% water + 75% boiled turmeric water), T4 (100% boiled turmeric water).The results showed that boiled turmeric water give significantly affect the percentage of lymphocytes and eosinophils (P<0,05), but did not significantly affect the total number of leukocytes, percentage of heterophile and monocytes (P>0,05). The conclusion from this study is that the boiled turmeric water in the drinking water of broilers was able to improve white blood profile, that indicated by the number of leukocyte and percentage of lymphocytes and eosinophils. Keywords: Turmeric, leuycocyte, differential leucocyte, broiler